PRACTICAL APPROACHES TO CALCULATION OF CONICAL ROOFS OF STEEL SILO CAPACITIES (Collection of scientific works «Modern structures of metal and wood», 2019)
This  article  deals  with  the  study  of  parameters  of  the  stress-strain  state  of  the elements  of  conical  roofs  of  the  cylindrical  silos.  They  are  mainly  made  of  the  thin  sheet  steel structures. On the basis of the finite element method modern design and calculation complexes of the strength analysis allow easily and with sufficient accuracy perform such a calculation. However, in  some  cases  there  are  such  problems  when  using  a  computerized  data-entry  machine  rather complicates  the  decision  process.  The  alternative  is  to  solve  this  problem  in  a  simple  form  of analytical calculation. Though the result will have less accuracy, but it will significantly reduce both time and work load of a designer. This article considers a number of practical questions that occur in case of a constructive solution of the main radial rib of the roof in the form of a beam of the thin-walled  profile  or  a  construction  with  parallel  belts.  In  the  calculation  scheme  of  the  rib  it  was illustrated the features of considering the presence of three annular stiffeners and secondary beams. It was proposed a simplified procedure for estimating current loads, by replacing four sections of unevenly distributed load with one of equivalent action. The search of unknown internal forces in this calculation scheme is performed by the force method. The general algorithm lies in a consistent determination of efforts in the main radial rib from the single efforts; in calculation of parameters of equivalently  distributed  load;  in  finding  the  effort  functions  of  the  given  load  and  thermal suspension,  as  well  as  of  the  pressure  of  the  annular  stiffeners;  in  determining  the  horizontal displacements  of  points  of  disconnection  in  the  main  system  and  the  magnitude  of  the displacements; in calculation of unknown support reactions and determination of internal efforts for dangerous  sections.  The  numerical  implementation  allows  estimating  the  accuracy  of  this calculation.  Also  the  example  demonstrates  the  simplicity  of  its  implementation,  compared  to  a computer procedure based on the finite element method.